2010
DOI: 10.1007/s10212-010-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between teaching practices and student achievement in first year classes

Abstract: International audienceThis study investigated the links between the teaching practices of primary school teachers (n = 200) who were observed while presenting a new text to their first year classes, and the student achievement levels in those classes. The teaching practices are specifically concerned with the way the teachers supported and encouraged students’ activities during verbal interactions. Two different populations were observed: classes of first year students with a reduced teacher–student ratio (abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…The results from this study are aligned with the literature that class size impacts the amount of teacher-student interaction that CLASS SIZE IN P.E. 60 occur within a PE class (Clanet, 2010). In addition, the amount of individualized instruction that the teacher can provide to students was impacted, with participants noting that they frequently focused on whole group discussion rather than individualized instruction, which research has shown can negatively impact student learning (An and Meaney, 2015;Marinescu et al, 2014;& Rikard, 1992).…”
Section: Implications For the Literaturesupporting
confidence: 80%
See 1 more Smart Citation
“…The results from this study are aligned with the literature that class size impacts the amount of teacher-student interaction that CLASS SIZE IN P.E. 60 occur within a PE class (Clanet, 2010). In addition, the amount of individualized instruction that the teacher can provide to students was impacted, with participants noting that they frequently focused on whole group discussion rather than individualized instruction, which research has shown can negatively impact student learning (An and Meaney, 2015;Marinescu et al, 2014;& Rikard, 1992).…”
Section: Implications For the Literaturesupporting
confidence: 80%
“…Other factors contributing to successful learning and a positive learning environment include positive teacher student interactions. Clanet (2010) identified that teachers of smaller classes had more direct interaction with their students, with more individualized instruction occurring during these in class interactions. Smaller classes were observed to have a more positive learning environment, which facilitated student engagement and initiation of on task behavior.…”
mentioning
confidence: 99%
“…Having identified the various reading preferences of boys and girls and their association with reading achievement, we took a closer look at current educational practices in this regard. How we teach reading is particularly important because it is directly associated with student outcomes (Hairrell et al, 2011;Clanet, 2010;Palumbo & Sanacore, 2009). Our analysis hopefully sheds light on the similarities and differences between existing practices and the actual reading interests of boys and girls which may help to improve teaching methods in this regard.…”
Section: Teaching Practices and Reading Achievementmentioning
confidence: 99%